Inconvenient Truths, and Changes to Believe In: Foreword to the Forum - Jeannie Ma. Guerrero (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2009)
This is a foreword to four papers that originated in the special session, “Ethnic Diversity in Music Theory: Voices from the Field,” at the November 2007 meeting of the Society for Music Theory (Baltimore). Inspired by the impassioned discussion period following the talks, the Committee on Diversity arranged to publish these papers to capture the session’s energy and channel it into a more permanent medium. This foreword, written by the moderator, highlights several issues that surfaced in the papers and in the ensuing discussion. The issues coalesce into a call for new action: diversity efforts have not worked in the forms known, but with reengineering they are vital for securing a future in the SMT for all.